Customer awareness and acceptance towards Billion Marketing's in-house brand for leather products 'RORINE' / Mazumi Jaafar - Jaafar, Mazumi (1998)
In today's highly competitive retail industry, in-house brands products are becoming more and more important. As department stores and specialty outlets rely less on manufacturer brands and more on promoting their own in-house brands. In-house brands give the retailer greater control over the merchandise, more flexibility in dealing with changing trends, and more control over prices. This study is undertaken to determine customer awareness of RORINE brand (BM's in-house brand for leather products) and to determine the customer acceptance toward RORINE's prices, material quality, choice of color, designs and styles, and stitching quality. It is also to determine the factors of unawareness and the most effective promotion tools that are suitable for BM to promote their in-house brands. The findings indicate that majority of respondents are aware of RORINE brand. Their main source of information are from words of mouth. Majority of them perceived that the prices of RORINE are expensive but they are satisfied with the overall quality of RORINE products. The findings also show that majority of respondents who are not aware of RORINE state that the main factor of unawareness is lack of promotion and advertisement. As a result, some recommendations and suggestions are made to increase the customer awareness towards RORINE. The recommendations are: to use broadcast media such as television and radio, print media such as newspapers and magazines. Other recommendations are FBH or BM should introduce Personal Selling Module to train and motivate salespersons, and to increase the number of existing salespersons. To increase the customer level of acceptance, other recommendations are to reduce the prices of RORINE, to offer new range of leather products and more choices for the popular items.